Randomized Trial of First-Line Behavioral Intervention to Reduce Need for Medication in Children with ADHD. Issue 5 (2nd September 2020) - Coles, Erika K.; Pelham, William E.; Fabiano, Gregory A.; Gnagy, Elizabeth M.; Burrows-MacLean, Lisa; Wymbs, Brian T.; Chacko, Anil; Walker, Kathryn S.; Wymbs, Frances; Robb Mazzant, Jessica; Garefino, Allison; Hoffman, Martin T.; et al.
Abstract : A study conducted in an analogue summer treatment setting showed that when concurrently receiving behavioral intervention, many children with Attention-Deficit Hyperactivity Disorder (ADHD) did not need medication or maximized responsiveness at very low doses. The present study followed participants in that summer study into the subsequent school year to investigate whether the same pattern would extend to the natural school and home settings. There were 127 unmedicated children with ADHD between the ages of 5 and 13 who were randomly assigned to receive or not receive behavioral consultation (BC) at the start of the school year. Children were evaluated by teachers and parents each week to determine if central nervous system stimulant treatment was needed. Children who received BC were approximately half as likely those who did not (NoBC) to initiate medication use each week at school or home and used lower doses when medicated at school. This produced a 40% reduction in total methylphenidate exposure over the course of the school year. BC and NoBC groups did not significantly differ on end-of-year teacher or parent ratings of behavior, which were positive. Moreover, BC and NoBC groups did not significantly differ in cost of treatment; although children in the BC condition accrued additional costs via the BC, these costs were offset by the associated delay and reduction in medication use. Results add to a growing literature suggesting that the use of low-intensity behavioral intervention as a first-line treatment reduces or eliminates the need for medication in children with ADHD.